2021
DOI: 10.1016/j.heliyon.2021.e07111
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors and early marriage among women in Bangladesh, Ghana and Iraq: An illustration from Multiple Indicator Cluster Survey

Abstract: Early marriage is a form of violation of child rights to grow and develop. The Sustainable Development Goals had included early marriage in target 5.3, aiming to eliminate by 2030. This study examines the socio-demographic factors associated with women's early marriage in Bangladesh, Ghana, and Iraq using information extracted from 2019, 2017-2018, and 2018 Multiple Indicator Cluster Surveys (MICSs) of Bangladesh, Ghana, and Iraq, respectively. The chi-square test examined the association between socio-demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
6
18
0
Order By: Relevance
“…The results of the current study showed a highly statistically significant relationship between the knowledge of early marriage among female nursing students and their sociodemographic traits, including age, employment status, length of marriage, husband's age, mother's educational attainment, mother's occupation, father's educational attainment, and monthly income. This result was in accordance with Saleheen et al (22) study, in Bangladesh, Ghana, and Iraq (n=31060). They discovered a strong statistical relationship between the sociodemographic traits of females and their parents.…”
Section: Answer Research Question No (2) What Are the Risk Factors Fo...supporting
confidence: 93%
“…The results of the current study showed a highly statistically significant relationship between the knowledge of early marriage among female nursing students and their sociodemographic traits, including age, employment status, length of marriage, husband's age, mother's educational attainment, mother's occupation, father's educational attainment, and monthly income. This result was in accordance with Saleheen et al (22) study, in Bangladesh, Ghana, and Iraq (n=31060). They discovered a strong statistical relationship between the sociodemographic traits of females and their parents.…”
Section: Answer Research Question No (2) What Are the Risk Factors Fo...supporting
confidence: 93%
“…Several studies indicated a higher prevalence of child marriage among women living in rural areas (Saleheen et al. 2021). However, our study found no significant difference in child marriage between rural and urban respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Child marriage adversely impacts women’s economic opportunities [ 5 ], resulting in lower economic status for women who were married as children. Child brides also experience limited access to mass media [ 62 , 63 ]. Taken together, these studies illustrate the complexity of social, family, and gender dynamics in potentially affecting access to healthcare services for women who were married as children.…”
Section: Discussionmentioning
confidence: 99%